Pengembangan Aplikasi Ujian Fisika Berbasis Komputer untuk Meningkatkan Integritas Peserta Didik di SMA Islam Assa’adah - Khaerul Fuad; Irnin Agustina Dwi Astuti; Indica Yona Okyranida (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2021)
This study aims to develop a computer-based exam application using a template from the BeeSMART CBT application. The research method used in this research is a research and development method with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). This research has produced a computer-based exam application. Validation test results, this application is suitable for use. The average total score for the material expert validation assessment was 93.75%, and the total score average was 90.44% for the media expert validation assessment with each score included in the "very feasible" criteria. The response of students to assess the ease of use showed a score of 82.4%, and the ability of the application to prevent cheating was 81.7%. The results of teacher observations showed that the level of student cheating was 36.25%, which means that cheating was small, and the level of integrity was large.